TWO DIRECTIONS OF DEVELOPMENT OF THE HOT-ROLLED PLATE PRODUCTION - Andrey I. Rozhkov; Anton I. Rozhkov (Литьë и металлургия, 2010)
Two main directions of production of hot-rolled plate: foundry-rolled and schema «ore-semiproduct-rolled metal» are examined.